PENGARUH KEAHLIAN, INDEPENDENSI, DAN ETIKA TERHADAP KUALITAS AUDITOR PADA KAP SURABAYA - Pratiwi, Argitania Diah; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to examine the influence of expertise, independence, and ethics to the auditor quality. Theresearch object is the auditor in public accountant firm in Surabaya. The sources of primary data in this researchresponse to the questionnaires which have been issued to the auditors. This research is an empirical research inwhich the sample collection method is based on the consideration (judgment sampling) i.e. the sample collectionhas been done by using predetermined criteria, so 30 respondents have been selected as samples. The form of thequestionnaires which have been used in this research is closed questionnaire. The analysis technique has beendone by using multiple regression analysis. In this research, there are six variables which consist of fiveindependent variables i.e. expertise, independence, and ethics and one dependent variable i.e. auditor quality.Based on the result, it can be concluded that partially expertise, independence, and ethics have positive andsignificant influence to the auditor quality. and it is supported by the determination coefficient which indicatesthat expertise, independence, and ethics give influence to the dependent variable (auditor quality)simultaneously is 53.9%, whereas the remaining 46.1% is influenced by other factors.Keywords: expertise, independence, ethics, auditor quality